Health Status of 'Community Cats' Living in the Tourist Area of the Old Town in Onomichi City, Japan. Issue 4 (2nd October 2022) - Seo, Aira; Ueda, Yoshihide; Tanida, Hajime
ABSTRACT: The "community cat program (CCP)" is a non-lethal control measure in which stray cats are owned and cared for as community cats at high welfare standards, while the Trap-Neuter-Return (TNR) or Trap-Test-Vaccinate-Alter-Return-Monitor (TTVARM) event is performed. The program is recommended by the Ministry of the Environment in Japan. Here, we evaluated the health status of community cats inhabiting a tourist area in Onomichi City. A medical check was conducted on 30 community cats as a part of the TTVARM event. The following health problems were identified: alopecia, gingivitis, incisor teeth loss, anemia, and urine glucose. An ELISA (the enzyme linked immunosorbent assay) showed that 16.7% of the cats were FIV-positive. The cats were also carriers of zoonoses ( Capnocytophaga genus (100%) and Bartonella henselae ( ITS, nested; 38.0%)), which pose a risk to tourists and residents. Our findings suggest that most cats require medical treatment. We recommend that friendly cats should be adopted rather than maintained as community cats and that a comprehensive review of the CCP is required.